Becoming neighbors in a Mexican American community : power, conflict, and solidarity - Ochoa, Gilda L (University of Texas Press, 2004)
On the surface, Mexican Americans and Mexican immigrants to the United States seem to share a common cultural identity but often make uneasy neighbors. Discrimination and assimilationist policies have influenced generations of Mexican Americans so that some now fear that the status they have gained by assimilating into American society will be jeopardized by Spanish-speaking newcomers. Other Mexican Americans, however, adopt a position of group solidarity and work to better the social conditions and educational opportunities of Mexican immigrants. Focusing on the Mexican-origin, working-class city of La Puente in Los Angeles County, California, this book examines Mexican Americans’ everyday attitudes toward and interactions with Mexican immigrants—a topic that has so far received little serious study. Using in-depth interviews, participant observations, school board meeting minutes, and other historical documents, Gilda Ochoa investigates how Mexican Americans are negotiating their relationships with immigrants at an interpersonal level in the places where they shop, worship, learn, and raise their families. This research into daily lives highlights the centrality of women in the process of negotiating and building communities and sheds new light on identity formation and group mobilization in the U.S. and on educational issues, especially bilingual education. It also complements previous studies on the impact of immigration on the wages and employment opportunities of Mexican Americans.